Host immune responses in aged rhesus macaques against BBV152, an inactivated SARS-CoV-2 vaccine, and cross-neutralization with beta and delta variants - Patil, Dilip R.; Shete, Anita M.; Yadav, Pragya D.; Sapkal, Gajanan N.; Deshpande, Gururaj R.; Kaushal, Himanshu; Mohandas, Sreelekshmy; Fulari, Siddharam; Jain, Rajlaxmi; Kumar, Ajay; Abraham, Priya (Frontiers in Immunology, 2023)
The magnitude and duration of immune response to COVID-19 vaccination in older adults are known to be adversely affected due to immunosenescence and inflammaging. The threat of emerging variants warrants studies on immune response in older adults to primary vaccination and booster doses so as to understand the effectiveness of vaccines in countering the threat of emerging variants. Non-human primates (NHPs) are ideal translational models, as the immunological responses in NHPs are similar to those in humans, so it enables us to understand host immune responses to the vaccine. We initially studied humoral immune responses in aged rhesus macaques employing a three-dose regimen of BBV152, an inactivated SARS-CoV-2 vaccine. Initially, the study investigated whether the third dose enhances the neutralizing antibody (Nab) titer against the homologous virus strain (B.1) and variants of concern (Beta and Delta variants) in aged rhesus macaques immunized with BBV152, adjuvanted with Algel/Algel-IMDG (imidazoquinoline). Later, we also attempted to understand cellular immunity in terms of lymphoproliferation against γ-inactivated SARS-CoV-2 B.1 and delta in naïve and vaccinated rhesus macaques after a year of the third dose. Following the three-dose regimen with 6 µg of BBV152 with Algel-IMDG, animals had increased Nab responses across all SARS-CoV-2 variants studied, which suggested the importance of booster dose for the enhanced immune response against SARS-CoV-2-circulating variants. The study also revealed the pronounced cellular immunity against B.1 and delta variants of SARS-CoV-2 in the aged rhesus macaques even after a year of vaccination.